Genome-Wide Differences in DNA Methylation Changes in Two Contrasting Rice Genotypes in Response to Drought Conditions - Wang, Wensheng; Qin, Qiao; Sun, Fan; Wang, Yinxiao; Xu, Dandan; Li, Zhikang; Fu, Binying (Frontiers in Plant Science, 2016)
Differences in drought stress tolerance within diverse rice genotypes have been attributed to genetic diversity and epigenetic alterations. DNA methylation is an important epigenetic modification that influences diverse biological processes, but its effects on rice drought stress tolerance are poorly understood. In this study, methylated DNA immunoprecipitation sequencing and an Affymetrix GeneChip rice genome array were used to profile the DNA methylation patterns and transcriptomes of the drought-tolerant introgression line DK151 and its drought-sensitive recurrent parent IR64 under drought and control conditions. The introgression of donor genomic DNA induced genome-wide DNA methylation changes in DK151 plants. A total of 1190 differentially methylated regions (DMRs) were detected between the two genotypes under normal growth conditions, and the DMR-associated genes in DK151 plants were mainly related to stress response, programmed cell death, and nutrient reservoir activity, which are implicated to constitutive drought stress tolerance. A comparison of the DNA methylation changes in the two genotypes under drought conditions indicated that DK151 plants have a more stable methylome, with only 92 drought-induced DMRs, than IR64 plants with 506 DMRs. Gene ontology analyses of the DMR-associated genes in drought-stressed plants revealed that changes to the DNA methylation status of genotype-specific genes are associated with the epigenetic regulation of drought stress responses. Transcriptome analysis further helped to identify a set of 12 and 23 DMR-associated genes that were differentially expressed in DK151 and IR64, respectively, under drought stress compared with respective controls. Correlation analysis indicated that DNA methylation has various effects on gene expression, implying that it affects gene expression directly or indirectly through diverse regulatory pathways. Our results indicate that drought-induced alterations to DNA methylation may influence an epigenetic mechanism that regulates the expression of unique genes responsible for drought stress tolerance.